Beyond The New Public Management: Changing Ideas and Practices in Governance (Edward Elgar, 1988)
Beyond the New Public Management is an important book which provides a comprehensive analysis of current conceptual debates in public management and governance; and critically reviews attempts made over the last two decades to apply the `new public management' model in developed and developing countries. The book brings together a number of outstanding specialists who examine the range of ideas and concepts of the new models of reform, paying particular attention to the `new public management' model and to strategies of good governance. It evaluates progress made by governments and aid donors in putting these ideas into practice. Using case studies from both the developed and developing world, it emphasises the extent to which public management and governance reforms are being applied throughout the international arena. The examples used focus on the problems of policy and institutional transfers between the industrialised world and developing countries. Multidisciplinary in its approach, the book draws on literature and research from management studies, political science, sociology, economics and development studies; and points to issues likely to dominate the future research agenda. This thoughtful and wide-ranging book will be essential reading for academics, students and practitioners of public management, public policy, governance and development.